Correlations between pH and per cent base saturation of some Brazilian soils - Castro, Abeilard Fernando de; Barreto, Washington de Oliveira; Anastácio, Maria de Lourdes Amoroso (Pesquisa Agropecuaria Brasileira, 2014)
Soil samples from different horizons of several taxonomic units of Brazilian soils were used to study the correlations between percent base saturation and pH values determined in water, normal KCl solution, and 0,01 molar CaCl2 solution. Two different percent base saturation values were obtained, depending on the pH of the used in determining the exchangeable soil acidity. Exchangeable acidity was measured at pH = 7.0 and pH = 8.2, using normal calcium acetate and barium chloride-trietha-nolamine, respectively. The summation of the bases, calcium, magnesium, potassium, and sodium (S value) with the respective exchangeable soil acidity values, gave the cation exchange capacity (T value) at pH = 7.0 and 8.2, respectively. Through calculation, two different per cent base saturation values were obtained, represented by V7,0 and V8,2. The correlations obtained with the 158 soil samples, regardless the horizon or the taxonomic unit, were significant. The higher r values were obtained when the pH values were determined in 0.01 molar CaCl2 solution. From the total 158 soil samples, 60 were selected (30 B horizons of red yellow podzolic and 30 B horizons of latosol) to study the above correlations. The correlations of the red yellow podzolic soil were significant; the higher r values being obtained when the pH values were determined in 0.01 molar CaCl2 solution. However, the correlations using the latosols samples were not significant in all cases. The correlations with A horizon (58 samples), regardless the taxonomic unit, were highly significant and the r values were the highest obtained in this study. The correlation coefficient between V7,0 and V8,2 was 0,944xx; the regression equation obtained in the calculation was V7,0 = 9,26 + 1,26 V8,2.